2015
DOI: 10.1007/s13197-015-1736-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat Gouda cheese made from bovine milk-olive oil emulsion: physicochemical and sensory attributes

Abstract: The objective of this paper is to study the effect of milk-fat replacement on Gouda cheeses composition, lipolysis and sensory characteristics. A Gouda cheese-like product was prepared from the substitution of milk fat with emulsified olive oil. For comparison, the low-fat variant without fat replacers and the full-fat cheese were also studied. Milk samples are initially pasteurized at 72°C for 3 s, cooled to 35°C, and added with 0.016 g L −1 of lactic ferments and 0.30 mL L −1 of microbial rennet. Total solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
7
11
2
Order By: Relevance
“…No significant effect was noticed on appearance and odor scores between experimental cheeses (p<0.05). This result is opposite to our previous findings on low-fat Gouda cheese-like product (Felfoul et al, 2015). These differences could be attributed to the difference in the studied cheese types as well as the higher moisture content found in white brined cheese compared to that of Gouda cheese which might influence positively the mouthfeel attributes.…”
Section: Sensory Evaluation Of the Cheesescontrasting
confidence: 99%
See 4 more Smart Citations
“…No significant effect was noticed on appearance and odor scores between experimental cheeses (p<0.05). This result is opposite to our previous findings on low-fat Gouda cheese-like product (Felfoul et al, 2015). These differences could be attributed to the difference in the studied cheese types as well as the higher moisture content found in white brined cheese compared to that of Gouda cheese which might influence positively the mouthfeel attributes.…”
Section: Sensory Evaluation Of the Cheesescontrasting
confidence: 99%
“…Thus, it can be concluded that fat replacers could play a very important role in fat retention. This result was in accordance with those reported by Romeih et al (2002) and Felfoul et al (2015). With regard to L obatoCalleros et al (2003), they indicated that full-fat cheese has a significantly higher fat content than that of the obtained cheeses with canola oil having a high initial fat content.…”
Section: Physicochemical Characterization Of the Cheesessupporting
confidence: 91%
See 3 more Smart Citations